Antipas (Biblical archaeology review, 2021)
The article discusses the word Antipas, a nickname of a first-century ruler of Galilee and Perea whose name was Herod Antipatros that can be translated as Herod who is equal to his father, while in the New Testament, Antipas is involved in the executions of John the Baptist and Jesus of Nazare.